Newborn Screening for SCID and Other Severe Primary Immunodeficiency in the Polish-German Transborder Area: Experience From the First 14 Months of Collaboration - Giżewska, Maria; Durda, Katarzyna; Winter, Theresa; Ostrowska, Iwona; Ołtarzewski, Mariusz; Klein, Jeannette; Blankenstein, Oliver; Romanowska, Hanna; Krzywińska-Zdeb, Elżbieta; Patalan, Michał Filip; Bartkowiak, Elżbieta; Szczerba, Natalia; et al. (Frontiers in Immunology, 2020)
In 2017, in the Polish-German transborder area of West Pomerania, Mecklenburg-Western Pomerania and Brandenburg in collaboration with two centers in Warsaw, a partnership in the field of newborn screening (NBS) for severe primary immunodeficiency diseases (PID), mainly severe combined immunodeficiency (SCID) was initiated. SCID, but also some other severe PID, is a group of disorders characterized by the absence of T and/or B and NK cells. Affected infants are susceptible to life-threatening infections, but early detection gives a chance for effective treatment. A prevalence of SCID in the Polish and German populations is unknown but can be comparable to other countries (1:50 000 – 100 000). SCID NBS test is based on real-time polymerase chain reaction (qPCR) and measurement of a number of T cell receptor excision circles (TREC), kappa-deleting recombination excision circles (KREC) and beta-actin (ACTB) as a quality marker of DNA. This method can be effective also in NBS for other severe PID with T- and/or B-cell lymphopenia, including combined immunodeficiency (CID) or agammaglobulinemia. During 14 months of collaboration, 44287 newborns were screened according to the ImmunoIVD protocol. Within 65 positive samples – seven were classified to immediate recall and 58 requested a second sample. Examination of 58 second samples resulted in recalling of one newborn. Confirmatory tests included immunophenotyping of lymphocyte subsets with extension to TCR repertoire, lymphoproliferation tests, radiosensivity tests, maternal engraftment assays and molecular tests. Final diagnosis included: one case of T-BlowNK+ SCID, one case of atypical Tlow BlowNK+ CID, one case of autosomal recessive agammaglobulinemia and one case of Nijmegen breakage syndrome. Among four other positive results, three infants presented T- and/or B-cell lymphopenia due to either mother’s immunosuppression, prematurity or unknown reason, which resolved or almost normalized in the first months of life. One newborn was classified as truly false positive. The overall positive predictive value (PPV) for the diagnosis of severe PID was 50.0%. This is the first population screening study that allowed identification of newborns with T and/or B immunodeficiency in Central and Eastern Europe.